Switchable aerobic/anaerobic multi-substrate biofuel cell operating on anodic and cathodic enzymatic cascade assemblies - Herkendell, Katharina; Tel-Vered, Ran; Stemmer, Andreas (Nanoscale, 2017)
Enzymatic fuel cells may become more accessible for applications powering portable electronic devices by broadening the range of potentially usable fuels and oxidizers. In this work we demonstrate the operation of an integrated, yet versatile multi-substrate biofuel cell utilizing either glucose, fructose, sucrose or combinations of thereof as biofuels, and molecular oxygen originating from solution phase and/or an internal chemical source, as the oxidizer. In order to achieve this goal we designed an enzymatic cascade-functionalized anode consisting of invertase (INV), mutarotase (MUT), glucose oxidase (GOX), and fructose dehydrogenase (FDH), deposited on top of a mesoporous carbon nanoparticle matrix, in which electron relay molecules had been entrapped. The anode was then conjugated to a compatible enzymatic cathode that employs a cascade of catalase (CAT) and bilirubin oxidase (BOD), allowing the cell to operate in an aerobic environment and/or to utilize, under anaerobic conditions for instance, hydrogen peroxide as a source for the oxygen oxidizer. While operated in the presence of the sugar mixture and hydrogen peroxide, the power output of the dually cascaded biofuel cell reaches a peak power density of 0.25 mW cm-2 and demonstrates an open circuit potential of 0.65 V. To our knowledge this is the first reported biofuel cell that discharges with both anodic and cathodic enzymatic cascade architectures and the first biofuel cell that is repeatedly switched between aerobic and anaerobic conditions without any significant decrease in the discharge performance.
Created from Fastlane, Scopus look-up